2018
DOI: 10.3390/pharmaceutics10030149
|View full text |Cite
|
Sign up to set email alerts
|

Co-Amorphous Screening for the Solubility Enhancement of Poorly Water-Soluble Mirabegron and Investigation of Their Intermolecular Interactions and Dissolution Behaviors

Abstract: In the present study, the screening of Mirabegron (MBR) co-amorphous was performed to produce water-soluble and thermodynamically stable MBR co-amorphous with the purpose of overcoming the water solubility problem of MBR. MBR is Biopharmaceutics Classification System (BCS) class II drug used for the treatment of an overreactive bladder. The co-amorphous screening was carried out by means of the vacuum evaporation crystallization technique in methanol solvent using three water-soluble carboxylic acids, characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 25 publications
(39 reference statements)
1
20
0
2
Order By: Relevance
“…The co-amorphous systems involve combining drug and low molecular weight organic excipient (the co-former) in an equimolar ratio using suitable methods to yield a homogenous amorphous single phase [27][28][29]. It should be noted that several studies have established the ability of citric acid and tartaric acid to form co-amorphous systems with weakly basic drugs [30][31][32][33], which corroborates our results on the formation of BX795-tartaric acid/citric acid co-amorphous systems. Furthermore, our PXRD analyses showed that BX795-tartaric acid/citric acid co-amorphous mixtures were stable for at least 1 month at room temperature (Figure S18).…”
Section: Discussionsupporting
confidence: 89%
“…The co-amorphous systems involve combining drug and low molecular weight organic excipient (the co-former) in an equimolar ratio using suitable methods to yield a homogenous amorphous single phase [27][28][29]. It should be noted that several studies have established the ability of citric acid and tartaric acid to form co-amorphous systems with weakly basic drugs [30][31][32][33], which corroborates our results on the formation of BX795-tartaric acid/citric acid co-amorphous systems. Furthermore, our PXRD analyses showed that BX795-tartaric acid/citric acid co-amorphous mixtures were stable for at least 1 month at room temperature (Figure S18).…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, conversion of a crystalline drug into an amorphous form could improve its water solubility. 34 As shown in Figure 3 , EE- and PVA-encapsulated PTS changed the crystalline nature of raw PTS to the amorphous form. Additionally, it is well known that the formation of hydrogen bonds between nanocarriers and lipophilic bioactive compounds could effectively enhance the water solubility of the raw compound.…”
Section: Discussionmentioning
confidence: 92%
“…Drug–organic acid CAMS form the third largest class of the reported CAMS with 12.9%. Organic acids have been applied as co-formers in CAMS mainly as acidic excipients to form strong molecular interactions with basic drugs (for example in [ 25 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]). The organic acids used as co-formers differ in their number of carboxylic acid groups, which was hypothesized to lead to salt formation with a basic drug at different molar ratios.…”
Section: Classes Of Investigated Camsmentioning
confidence: 99%